2014
DOI: 10.1542/hpeds.2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vancomycin Dosing and Corresponding Drug Concentrations in Pediatric Patients

Abstract: The number of trough concentrations within the target range of 10 to 20 μg/mL was low, and younger patients often needed doses >60 mg/kg per day to achieve a trough concentration in this range. The dose of vancomycin was found to have a statistically significant effect on the ability to achieve a trough concentration within the target range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“…First, it has relatively small numbers and was conducted at a single clinical center, which limits its generalizability. However, as previously stated, several previous studies have found similar deficiencies in vancomycin practices based on retrospective analyses, 3 and, as a quality improvement project, these numbers should be sufficient to determine control limits and provide appropriate information regarding the stability of a process. A second limitation was the exclusion of patients with unpredictable volume of distribution, such as patients requiring vasopressor support, and patients with increased potential for nephrotoxicity, such as those with kidney disease, cystic fibrosis, and concomitant therapy with an aminoglycoside.…”
Section: Figurementioning
confidence: 74%
See 2 more Smart Citations
“…First, it has relatively small numbers and was conducted at a single clinical center, which limits its generalizability. However, as previously stated, several previous studies have found similar deficiencies in vancomycin practices based on retrospective analyses, 3 and, as a quality improvement project, these numbers should be sufficient to determine control limits and provide appropriate information regarding the stability of a process. A second limitation was the exclusion of patients with unpredictable volume of distribution, such as patients requiring vasopressor support, and patients with increased potential for nephrotoxicity, such as those with kidney disease, cystic fibrosis, and concomitant therapy with an aminoglycoside.…”
Section: Figurementioning
confidence: 74%
“…was 15 mg/kg every 6 hours for pediatric patients. 2 It is unclear, however, if the high trough goal can be reliably attained by using the suggested dosing 3,4 and if the use of higher doses will improve target attainment within a clinically appropriate time interval.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A therapeutic vancomycin initial trough level was defined as 10 to 20 µg/mL. 10,12,15 Pediatric inpatients aged 1 month to 12 years at the time of starting vancomycin which was received during the period from 1 February 2016 to 31 January 2017 were included. They must have received at least three vancomycin doses of 15 mg/kg/dose every 6 h (intended total daily dose of 60 mg/kg/day divided every 6 h).…”
Section: Methodsmentioning
confidence: 99%
“…Eligible patients were then categorized into three age groups for the secondary outcomes: Group (1): ⩾1 month to 23 months, group (2): 2-5.99 years, and group (3): 6-12.99 years. 10,12 For convenience, ages 2-5.99 and 6-12.99 years will be expressed all through as 2-5 and 6-12 years, respectively.…”
Section: Methodsmentioning
confidence: 99%